2016
DOI: 10.1097/md.0000000000003386
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Pathological, and Prognostic Characteristics of Glomerulonephritis Related to Staphylococcal Infection

Abstract: Staphylococcal infection has become a common cause of postinfectious glomerulonephritis in the past 3 decades. Because few investigations focus on this disease, the demographics and clinicopathological features of glomerulonephritis related to staphylococcal infection are not well characterized.We conducted a pooled analysis of published literature in electronic databases and analyzed the clinical features, laboratory findings, and histopathological changes. The patients were divided into 4 groups based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 57 publications
3
33
0
1
Order By: Relevance
“…Microbial populations of Candida albicans and Staphylococcus aureus were found to be higher and more persistent in diabetic rats [9,10]; in contrast, renal enterococcal populations were similarly sustained in both diabetic and control rats. Neither the duration of the diabetic state nor weight loss was found to be a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial populations of Candida albicans and Staphylococcus aureus were found to be higher and more persistent in diabetic rats [9,10]; in contrast, renal enterococcal populations were similarly sustained in both diabetic and control rats. Neither the duration of the diabetic state nor weight loss was found to be a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is comparable to previous results reporting that 75% to 86% of the patients are male with a mean age of 55 to 65 years. 9,10,12,[16][17][18][19][20] It must be noted that the youngest of our patients is a 5-year-old boy, indicating that IRGN-IgA, although rarely reported, can be observed in pediatric patients. In this case and in other reported pediatric cases, children with Staphylococcus-related GN had the same presentation as adults, namely proteinuria and renal function impairment.…”
Section: Discussionmentioning
confidence: 57%
“…[5][6][7][8] Post-staphylococcal glomerulonephritis (GN) can histologically appear with two patterns: one resembling acute poststreptococcal glomerulonephritis, due to Staphylococcus aureus infection and mostly associated with diabetes mellitus, neoplasia or alcoholism; the other with a membranoproliferative glomerulonephritis pattern in Staphylococcus epidermidis infection in patients with atrio-ventricular shunts. 8,9 However, a new presentation was first reported in 1980 by Spector et al and described in 2003 by Nasr et al in 5 patients with type 2 diabetes, Staphylococcus aureus infection, acute renal failure and histologic exudative endocapillary proliferation with predominant mesangial IgA deposits. 10 Since then, American or Asian teams have reported cases and cohorts of infection-related glomerulonephritis with dominant IgA deposits (IRGN-IgA) or codominant with C3 deposits.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, endocapillary proliferation (89% vs 23-63% in previous series) made of neutrophils in most cases (81% vs 15 to 63% of the biopsies) was more frequent whereas pure mesangial proliferation was less frequent compared to other studies. 9,10,13,18,19,21 We also noticed differences when we compared histological patterns as classified in acute, subacute and resolving by Haas et al in 2008. 13 The authors reported more resolving and less acute or subacute patterns compared to our cohort, with 15% of acute, 23% of subacute and 62% of resolving GN vs 26%, 63% and 11% respectively in our cohort.…”
Section: Discussionmentioning
confidence: 82%
“…5−8 Post-staphylococcal glomerulonephritis (GN) can histologically appear with two patterns: one resembling acute poststreptococcal glomerulonephritis, mostly observed in patients with diabetes mellitus, neoplasia or those with chronic alcoholic consumption, infected with Staphylococcus aureus infection; the other corresponding to a membranoproliferative glomerulonephritis pattern in Staphylococcus epidermidis infection of atrio-ventricular shunt. 8,9 A third form was reported in 1980 by Spector et al, and described in 2003 by Nasr et al with 5 cases of type 2 diabetes patients with a Staphylococcus aureus infection, presenting with acute renal failure and histologic exudative endocapillary proliferation with predominant mesangial IgA deposits. 10,11 Since then, American or Asian teams reported cases and cohorts of infection-related glomerulonephritis with dominant IgA deposits (IRGN-IgA) or codominant with C3 deposits.…”
Section: Introductionmentioning
confidence: 99%